2019
DOI: 10.1001/jamanetworkopen.2018.7374
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Harsh Physical Punishment and Child Maltreatment in Childhood With Antisocial Behaviors in Adulthood

Abstract: Key Points Question Are harsh physical punishment in the absence of child maltreatment and child maltreatment with and without harsh physical punishment in childhood associated with antisocial behaviors in adulthood? Findings In this cross-sectional study using nationally representative data on 36 309 adults, harsh physical punishment in the absence of child maltreatment and child maltreatment that they had experienced were associated with antisocial behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
3
17
0
3
Order By: Relevance
“…Additionally, this study contributes to the literature, by examining the clinical entity of complex and severe depression, which demands specialized, multidisciplinary, and highly intensive mental health care (National Institute for Health and Care Excellence, 2009). Furthermore, we found that harsh physical punishment and sexual contact with a nonrelative were independently associated to these complex clinical presentations of depression in adulthood, confirming the deleterious long‐term mental health outcomes of these specific types of childhood and adolescent traumatic events (Afifi et al, 2014, 2019; Hailes et al, 2019; Ng et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, this study contributes to the literature, by examining the clinical entity of complex and severe depression, which demands specialized, multidisciplinary, and highly intensive mental health care (National Institute for Health and Care Excellence, 2009). Furthermore, we found that harsh physical punishment and sexual contact with a nonrelative were independently associated to these complex clinical presentations of depression in adulthood, confirming the deleterious long‐term mental health outcomes of these specific types of childhood and adolescent traumatic events (Afifi et al, 2014, 2019; Hailes et al, 2019; Ng et al, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…A crosssectional study of more than 36 000 US men and women suggested that nearly half of antisocial behaviours in adults could be accounted for by harsh physical punishment or maltreatment when they were children. 128 Society has a responsibility to protect children from violence within families, but worldwide govern ment intervention into intimate family situations for child maltreatment falls heaviest on marginalised popu lations, including indigenous families, and racial and sexual minorities. Further, domestic violence is more concentrated in communities that experience poverty and street violence and have poor access to services, yet the harm done to children by family separation, particularly for indigenous and minority populations, must also be understood as a type of structural violence.…”
Section: Families' Rights and Responsibilities In Nurturing Their Chimentioning
confidence: 99%
“…Such experiences include emotional, physical, and sexual abuse; household dysfunction; and neglect. Research studies from high-income countries (HICs) have shown robust associations between ACEs and adverse mental health outcomes in adulthood, including antisocial behaviors [ 8 ], adult life stress [ 9 ], smoking [ 10 ], problematic substance use [ 11 ], depression [ 12 ], and suicide [ 13 ]. Research has found that ACEs increase children and adolescents’ risk of having low resilience factors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%